Dual link distributed source coding scheme for the transmission of satellite hyperspectral imagery - Hagag, Ahmed; Omara, Ibrahim; Chaib, Souleyman; Ma, Guangzhi; El-Samie, Fathi E. Abd (Journal of visual communication and image representation, 2021)
•The problem of hyperspectral image lossless compression is highlighted.•A dual link distributed source coding (DLDSC) scheme is developed to improve hyperspectral images' lossless compression.•DLDSC removed the temporal redundancy concerning images of the same area captured at different instants of time.•Simulation results validate the effectiveness of the DLDSC over the the-state-of-art methods. Traditional lossless compression methods for satellite hyperspectral imagery focus on exploiting spatial and/or spectral redundancy. Those methods do not consider the temporal redundancy between images of the same area that are captured at different times. To exploit the temporal redundancy between hyperspectral images and reduce the amount of information to be transmitted from the space-satellite to the ground station via the downlink, this paper introduces a dual link distributed source coding (DLDSC) scheme for hyperspectral space-satellite communication. The proposed scheme employs the space-satellite dual link (i.e., the downlink and the uplink). The satellite onboard uses some side information from the ground station to calculate the hyperspectral image band coset values, and then, without syndrome coding, transmits to the ground station via the downlink. Coset coding is a typical technique used in distributed source coding (DSC), and here the coset values represent the timely hyperspectral image details. Typically, the coset values have lower entropy than that of the original source values. To exploit the temporal redundancy, the side information is computed in the ground station using the image captured at the previous time for the same area and transmitted to the space-satellite via the uplink. Hyperspectral images from the Hyperion satellite are used for the validation of the proposed scheme. The experimental results indicate that the proposed DLDSC scheme can reduce the original signal entropy by approximately 3.2 bits per sample (bps) and can achieve up to 1.0 bps and 1.6 bps gains over the lossless JPEG2000 standard and the state-of-art predictive CCSDS-123 method, respectively.